Fikih Hukum Tata Negara (Analisis Terhadap Mahkamah Syar’iyah di Aceh dalam Sistem Hukum Tata Negara Republik Indonesia) - Miftahul ulum (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2016)
General Explanation of Law Number 11 Year 2006 concerning Aceh Government stated that the trip constitutional Republic of Indonesia put Aceh as a unit of regional government that are special and specific, relating to the distinctive character of the historical struggle of the people of Aceh who have endurance and perseverance. Aceh's community life, articulated in a modern perspective of the state and government to be democratic and accountable. Such order of life is the embodiment in the motto Unity in Diversity. Keppres not have the capacity to regulate the power and authority of the judiciary especially Shari'a Courts in Nanggroe Aceh Darussalam. This is because the law has expressly delegated to the Qanun Aceh province to regulate the authority of the Court Syar'iyah based benchmark defined solely by the law that is based on the Islamic Shariah. But if we are concerned about the progress of the preparatory steps undertaken in order to take over its jurisdiction by the Court and the District Court Syar'iyah is still far from optimal, so for the time given device either incomplete legislation, secretariat and other Syari'yah Court administration still seems to take longer for the Court Syari'yah Aceh province can take over completely the authority of the District Court.